The effect of the use of Differentiated Instruction-Based Module on students’ learning motivation - Harmini, Triana; Effendi, Lukman (Unnes Journal of Mathematics Education, 2018)
The use of modules as teaching materials in the learning process is very important in order to improve the learning outcomes. The differentiated instruction based module is a learning module that differentiates instruction based on the differences of students ability level. Thereupon, the objectives of this study were: (1) to find out the differences of students' mathematics learning motivation before and after the use of differentiated instruction-based module, (2) to determine the effect of using differentiated instruction-based learning module on students’ mathematics learning motivation. This study used a quantitative approach and mathematics learning motivation questionnaire as the technique of collecting data. Also, to analyze the data this study used the T-Test (paired Samples T-Test) with the prerequisite of analysis, namely the normality and homogeneity test. Eventually, the results of analysis prerequisite analysis showed that both data were normally distributed and homogeneous. Meanwhile, the results of the t-test showed that there were significant differences between students’ mathematics learning motivation before and after the use of the differentiated instruction based learning module.